2008
DOI: 10.1177/1533317507307173
|View full text |Cite
|
Sign up to set email alerts
|

The Mini-Mental State Examination in Behavioral Variant Frontotemporal Dementia and Primary Progressive Aphasia

Abstract: There is little information regarding the usefulness of the Mini-Mental State Examination (MMSE) for tracking progression of non-Alzheimer's disease dementias. This study examined the utility of the MMSE in capturing disease severity in the behavioral variant frontotemporal dementia (bvFTD) and primary progressive aphasia (PPA), 2 nonamnestic clinical dementia syndromes. Retrospective data from 41 bvFTD and 30 PPA patients were analyzed. bvFTD patients' change in MMSE scores over time was significantly correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 26 publications
5
55
0
1
Order By: Relevance
“…Moreover, patients may have good compensatory abilities, which help them cope with aphasic problems in daily life. These findings are in line with Osher et al (2008), and Mioshi et al (2007). Clinicians should take this verbal handicap into account when testing cognitive status in people with aphasia and make better use of non-verbal cognitive tests like the Aphasia Check List (ACL) (Kalbe et al, 2005).…”
Section: Discussionsupporting
confidence: 73%
“…Moreover, patients may have good compensatory abilities, which help them cope with aphasic problems in daily life. These findings are in line with Osher et al (2008), and Mioshi et al (2007). Clinicians should take this verbal handicap into account when testing cognitive status in people with aphasia and make better use of non-verbal cognitive tests like the Aphasia Check List (ACL) (Kalbe et al, 2005).…”
Section: Discussionsupporting
confidence: 73%
“…It suffers from both floor and ceiling effects [26], though these should not be of particular concern for the trials included in this study. In addition, it is particularly suitable for measuring the cognitive deficits observed in AD and may be less sensitive to those in VaD [27] or FTD [28]. However, the latter has little impact in the current review, since only one included trial concerned FTD and, as mentioned, no significant differences were found between AD and VaD subgroups in the meta-regressions.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-two of the 26 PPA participants achieved a score of 24 or higher on the MMSE, indicating normal performance. The re-maining four achieved scores between 16 and 23, suggesting mild impairment, (but importantly, scores on this measure are influenced by patients' compromised language ability [23,45]). …”
Section: Experiments 1 Patterns Of Sentence Comprehension and Productionmentioning
confidence: 99%